Flow patterns in the Chukchi Sea based on an ocean reanalysis, June through October 1979–2014. (June 2018) - Bond, Nicholas; Stabeno, Phyllis; Napp, Jeffrey
Abstract: The oceanography of the Arctic is changing, with the potential to restructure the function and production of its ecosystems. The physical oceanographic conditions that have occurred on the Chukchi Sea shelf during June through October of the years 1979–2014 were investigated using the ORAS4 ocean reanalysis product. Time series of vertically integrated temperatures (especially during September and October) indicate greater warming in the first half of the 36-year record. This change in the long-term temperature trend may be in part due to trends in the mean currents, which in Herald Canyon and off the coast of Northwest Alaska tended to be slightly less poleward after 2000. A k-means cluster analysis of monthly mean sea surface height anomaly distributions was used to describe five distinct patterns of flow. Two of the five patterns (clusters 2 and 4) relate to the strength of the Alaskan Coastal Current (ACC). Another pair of patterns (clusters 3 and 5) had their strongest expressions in the northwest Chukchi Sea and relate to periods of weak southeastward versus strong northwestward flow in this region associated with the presence or absence of the Siberian Coastal Current. The fifth pattern (cluster 1) was defined by weak southeastward flow anomalies in the western Chukchi and a slightly suppressed ACC relative to the mean in the eastern Chukchi Sea. The composite sea surface height anomaly patterns of the five cluster types correspond closely with the mean sea level pressure anomaly distributions during the months constituting each cluster type. Our findings for the Chukchi Sea region provide a long-term context for previous field observations and may be useful for interpretation of past ecosystem variations.